2007
DOI: 10.1002/mds.21720
|View full text |Cite
|
Sign up to set email alerts
|

The role of executive function and attention in gait

Abstract: Until recently, gait was generally viewed as a largely automated motor task, requiring minimal higher-level cognitive input. Increasing evidence, however, links alterations in executive function and attention to gait disturbances. This review discusses the role of executive function and attention in healthy walking and gait disorders while summarizing the relevant, recent literature. We describe the variety of gait disorders that may be associated with different aspects of executive function, and discuss the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

76
1,448
11
62

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,714 publications
(1,597 citation statements)
references
References 146 publications
76
1,448
11
62
Order By: Relevance
“…Although gait has initially been considered a largely automatic action regulated mainly by subcortical control mechanisms including the brainstem and spinal cord (Armstrong, 1988;Grillner and Wallen, 1985), recent work has highlighted the influence of attention, executive function and other cognitive mechanisms (Hausdorff, 2005;Shaw, 2002;Yogev-Seligmann et al, 2008). Walking is a complex task involving the integration of locomotion, balance, and adaptation in an ever-changing environment (Armstrong, 1988;Blanc et al, 1999;Drew et al, 2004).…”
Section: The Neuroscience Of Gait and Agencymentioning
confidence: 99%
See 1 more Smart Citation
“…Although gait has initially been considered a largely automatic action regulated mainly by subcortical control mechanisms including the brainstem and spinal cord (Armstrong, 1988;Grillner and Wallen, 1985), recent work has highlighted the influence of attention, executive function and other cognitive mechanisms (Hausdorff, 2005;Shaw, 2002;Yogev-Seligmann et al, 2008). Walking is a complex task involving the integration of locomotion, balance, and adaptation in an ever-changing environment (Armstrong, 1988;Blanc et al, 1999;Drew et al, 2004).…”
Section: The Neuroscience Of Gait and Agencymentioning
confidence: 99%
“…This is important as humans may perform many perceptual, motor, and cognitive tasks while walking, potentially causing performance in these tasks to decline or change. Additionally these secondary tasks have been shown to alter gait characteristics and even lead to freezing or falls (for comprehensive reviews see Woollacott and Shumway-Cook, 2002;and Yogev-Seligmann et al, 2008). Thus, cognitive tasks such as verbal fluency (Dubost et al, 2006), fine-motor movements (Yang et al, 2007), and arithmetics (van Iersel et al, 2007) have been shown to alter gait characteristics ranging from walking velocity, over stride-variability in length, time, or width, to stride-asymmetry ( (Dubost et al, 2006;Yang et al, 2007); van Iersel et al, 2007).…”
Section: The Neuroscience Of Gait and Agencymentioning
confidence: 99%
“…Our study adds further evidence along these lines, showing that trunk stability in people with MCI is affected during dual-task walking. Dual-task-related changes in gait performance were thought to occur because gait control requires cognition (Al-Yahya et al 2011;Yogev-Seligmann et al 2008). Dual-task walking has been shown to be associated with cognitive function, particularly executive function, among cognitively normal older adults and those with cognitive impairment (Doi et al 2014;Hausdorff et al 2008;van Iersel et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…To examine the requirement, numerous studies have used a dualtask paradigm, i.e., dual-task walking, that requires more attentional resources and executive functions than normal walking (for reviews, see Al-Yahya et al 2011;Yogev-Seligmann et al 2008). Executive function is achieved primarily through prefrontal cortex and refers to a variety of higher cognitive processes, including components of volition, planning, purposive action, and effective performance (Lezak 2004).…”
mentioning
confidence: 99%
“…In addition, in persons with diabetes who develop cognitive frailty, this will worsen the ability to adequately manage diabetes and thus accelerate physical frailty (26). Dual tasking is a condition in which persons with an executive function deficit have decreased control over their walking when required to carry out another task (27,28). Dual tasking represents one obvious interaction where both cognitive and physical frailty are synergistic with one another.…”
mentioning
confidence: 99%